Food composition data and public health. Issue 3 (23rd August 2015) - Swan, G.; Dodhia, S.; Farron‐Wilson, M.; Powell, N.; Bush, M.
Abstract: Government has funded a programme of nutrient analysis of foods for many decades and resulting data have been published in successive editions of M c C ance and W iddowson's The Composition of Foods . Latest data were published in the seventh summary edition of The Composition of Foods in 2014 and in a revised Composition of Foods Integrated Dataset in 2015. The main purpose of the nutrient analysis programme is to provide data to support estimation of nutrient intakes in the National Diet and Nutrition Survey and other dietary surveys. Changes in the nutrient content of the UK food supply over time are driven by a number of factors including reformulation of processed foods resulting from policies to improve public health. Up‐to‐date nutrient composition data are key to ensuring that estimates of nutrient intakes in UK dietary surveys remain robust.